2019
DOI: 10.1097/md.0000000000016206
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms to predict survival of stage IV tongue squamous cell carcinoma after surgery

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 32 publications
(33 reference statements)
1
28
0
Order By: Relevance
“…Nonetheless, this nomogram accurately predicted survival in OTSCC. For T4 OTSCC, Sun and colleagues reviewed again the SEER database and identified 1550 patients 12 . Age, race, marital status, tumor site, UICC/AJCC TNM status and RT were recognized as independent prognostic factors associated with OS as well as cancer‐specific survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, this nomogram accurately predicted survival in OTSCC. For T4 OTSCC, Sun and colleagues reviewed again the SEER database and identified 1550 patients 12 . Age, race, marital status, tumor site, UICC/AJCC TNM status and RT were recognized as independent prognostic factors associated with OS as well as cancer‐specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] In literature, nomograms prognosticating OTSCC have been described. [11][12][13] Of these, some do not incorporate depth of invasion (DOI) and other valuable pathological information, while others do not measure all endpoints, and none of them are based on the 8th edition of the UICC/AJCC staging system. As a result, none of them can be reliably applied in a clinical context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 66 match our eligibility criteria and were furtherly assessed by full-text reading. At the end of selection process, 6 articles were considered suitable for inclusion in this systematic review [ 20 , 21 , 22 , 23 , 24 , 25 ]. Details on the selection process and reasons for exclusion are shown on Figure 1 .The value of k-statistic resulted 0.87, indicating an excellent level of agreement between reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…Some nomograms reported in the previous studies assessed the association of preoperative lymphocyte-to-monocyte ratio or some other clinical features with survival in patients with OSCC [18][19][20]. Apart from those studies, there have been some other prognostic nomograms based on mRNA expression profiles from the public databases that improved predicting the prognosis of patients with OSCC [21][22][23]. All of these studies showed promising prospects in clinical applications.…”
Section: Discussionmentioning
confidence: 99%